2017
DOI: 10.1161/jaha.117.006042
|View full text |Cite
|
Sign up to set email alerts
|

CM352 Reduces Brain Damage and Improves Functional Recovery in a Rat Model of Intracerebral Hemorrhage

Abstract: BackgroundIntracerebral hemorrhage (ICH) is an acute neurological disorder with high mortality and no effective treatment. In addition to the initial bleeding event, rebleeding and hematoma expansion are associated with poor outcome in these patients. We studied the effectiveness of the new antifibrinolytic agent CM352, a short‐half‐life matrix metalloproteinase inhibitor, for achieving early hemostasis and improving functional recovery in a rat model of collagenase‐induced ICH.Methods and Results ICH was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 34 publications
2
24
0
3
Order By: Relevance
“…A serials of preclinical researches of MMP inhibitors like CM352 ( 88 , 166 168 ), and neuroprotectors such as NXY-059 ( 169 , 170 ), NSP-116 ( 171 ), erythropoietin ( 172 ), valproic acid ( 173 ), memantine ( 174 ), curcumin ( 175 ), albumin ( 176 ), and tuftsin fragment 1-3 ( 177 ) have shed light on the treatment of HE. However, further studies to confirm the effect of CM352 and neuroprotectors are needed, since some pre-clinic medicines failed in clinical trials.…”
Section: Othersmentioning
confidence: 99%
“…A serials of preclinical researches of MMP inhibitors like CM352 ( 88 , 166 168 ), and neuroprotectors such as NXY-059 ( 169 , 170 ), NSP-116 ( 171 ), erythropoietin ( 172 ), valproic acid ( 173 ), memantine ( 174 ), curcumin ( 175 ), albumin ( 176 ), and tuftsin fragment 1-3 ( 177 ) have shed light on the treatment of HE. However, further studies to confirm the effect of CM352 and neuroprotectors are needed, since some pre-clinic medicines failed in clinical trials.…”
Section: Othersmentioning
confidence: 99%
“…A first limitation of our study is that functional outcome was limited to the first 24 h. However, our study was focused on safety and particularly on the risks of acute hematoma expansion and acute ICP changes associated with a brief application of HDT15°. Moreover, long‐term outcome is directly dependent on acute hematoma expansion, early hematoma volume, and early neurologic status in rats as in humans [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…These findings support our previous data, where we found that a biomarker of the blood–brain barrier (matrix metalloproteinase‐9) was a mediator between hyperthermia and poor outcome in a heterogeneous population of patients with ICH . Recently, we reported an acute short‐term treatment with a new antifibrinolytic agent (CM352), which limits brain damage by reducing hematoma expansion leading to improved functional and neurological recovery in an ICH rat model .…”
Section: Discussionmentioning
confidence: 99%